SIMULASI POLA ALIRAN FLUIDA DALAM DAERAH DENGAN BATAS TIDAK TERATUR MENGGUNAKAN METODE ELEMEN HINGGA - Defrianto Defrianto; Dwi Putri Cahya Safitri (Komunikasi Fisika Indonesia, 2019)
Research of ideal fluid flow on irregular domain by variation mesh has been done. Laplace equation was used to model velocity potential and the gradient was used to velocity. Boundary condition for inlet was chosen to be 15 , while for outlet was 30  and Neumann boundary condition on lateral side. The developed model shows that uniform flow was happened on straight channel and free vortex on the curved one. The analytical and computational calculation has similar results, that is 23.7787  and 23.7792  The percentage of the difference is 2.8  wich is very small, therefore this method is accurate enough to model pattern of ideal fluid flow on irregular domain.